REE AND HFSE DISTRIBUTION IN ROCKS AND MINERALS FROM GRANULAR PERIDOTITE XENOLITHS IN THE UDACHNAYA KIMBERLITE PIPE - Solov'eva L.V.; Egorov K.N.; Gornova M.A.; Smirnova E.V. (My University, 2004)
Deep-seated xenoliths in kimberlites are traditionally subdivided into granular low-temperature and deformed high-temperature groups. Recently, the rare element geochemistry of rocks and minerals has been invoked more often for deciphering the petrogenesis of mantle rocks. The interpretation of major and rare element data is complicated by the intricate evolution of these rocks, which experienced metamorphic recystallization and episode of mantle metasomatism after solidification. This article presents new data on the distribution of some incompatible rare elements in rocks and minerals of granular spinel and garnet peridotites from the Udachnaya Pipe. Evidence of modal mantle metasomatism (superposed minerals) may be present or absent in these rocks and minerals.